The Role of Personal Growth Initiative in Students’ Lives and Implications for Educational Counselors - Ferianti; Nurihsan, Juntika; Setiawati; Habibi, Muhammad Nur (Bisma The Journal of Counseling, 2024)
Personal growth initiative (PGI) were born from positive psychology, which plays a role in the development of students and their lives. However, currently, no systematic review specifically discusses previous research on the role of PGI in students' lives and what advice is given to educational counselors regarding students' PGI. Therefore, this research aims to review a systematic review of the role of PGI in students' lives and its implications for educational counselors. The systematic review method with the systematic review and meta-analysis (PRISMA) protocol was used to collect data. Data was obtained through the Scopus database using the article title "Personal Growth Initiative" and article title, abstract, keywords "student" from 2013 to 2023. Of the total 80 articles found, 11 met the inclusion criteria and were discussed in this research. Based on a systematic review, the results show that in the student context, higher levels of PGI contribute to increased work engagement, self-control, and lower levels of smartphone addiction, psychological well-being, mental health help-seeking, well-being for international students, future life satisfaction and happiness, and post-traumatic growth. The implications for educational counselors are that they need to encourage students' PGI skills and provide specialized training to enhance PGI, such as Intentional Growth Training. This intervention will support students in developing a solid vocational identity, reducing the risk of smartphone addiction, coping with post-traumatic stress, and improving their psychological well-being. Additionally, counselors should assist international students in cultural adjustment to address acculturation challenges and enhance their overall well-being.